2011
DOI: 10.1039/c1cc13151f
|View full text |Cite
|
Sign up to set email alerts
|

Stable aluminium fluoride chelates with triazacyclononane derivatives proved by X-ray crystallography and 18F-labeling study

Abstract: A single crystal structure of an aluminium-fluoride complex of a model compound (NODA-benzyl) was studied to understand the co-ordination chemistry. Series of ligands with an extra carboxylic acid linker for biomolecule conjugation were studied for improved (18)F-labeling applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 18 publications
4
80
1
Order By: Relevance
“…We reported a facile method for 18 F-radiolabeling of peptides previously that involves the binding of a highly stable [ 18 F](AlF) 2+ complex to a metal-binding ligand bound to a peptide (McBride et al, 2009; McBride et al, 2010; Laverman et al, 2010; D’Souza et al, 2011a, 2011b; McBride et al, 2011), and two other groups have recently reported their results using this labeling approach (Liu et al 2011; Shetty et al 2011). This radiolabeling approach has the advantage of rapid binding to the ligand, does not require a dry-down step, and high specific activities can be obtained after a simple SPE purification step to remove unbound 18 F. The procedure does not require expensive automated equipment, but could be easily adapted for use with such equipment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported a facile method for 18 F-radiolabeling of peptides previously that involves the binding of a highly stable [ 18 F](AlF) 2+ complex to a metal-binding ligand bound to a peptide (McBride et al, 2009; McBride et al, 2010; Laverman et al, 2010; D’Souza et al, 2011a, 2011b; McBride et al, 2011), and two other groups have recently reported their results using this labeling approach (Liu et al 2011; Shetty et al 2011). This radiolabeling approach has the advantage of rapid binding to the ligand, does not require a dry-down step, and high specific activities can be obtained after a simple SPE purification step to remove unbound 18 F. The procedure does not require expensive automated equipment, but could be easily adapted for use with such equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Although this procedure allows peptides to be fluorinated in one simple step within 30 min, it requires agents to be heated to ~100 °C, which is unsuitable for most proteins and some peptides. We and others have found that an aromatic group attached to one of the nitrogen atoms of the cylcononane ring of the NODA can enhance the yield for the ([ 18 F]AlF) 2+ complexation compared to some alkyl and carboxyl substituents (D’Souza et al, 2011b; McBride et al, 2010: Shetty et al 2011). In this report, we explore the potential for labeling heat-labile compounds with ([ 18 F]AlF) 2+ , using a new ([ 18 F]AlF) 2+ -binding ligand that contains 1,4,7-triazacyclononane-1,4-diacetate (NODA) attached to a methyl phenylacetic acid group (MPA).…”
Section: Introductionmentioning
confidence: 98%
“…39 These characteristics have prompted an increased interest in IEDDA reactions for bioconjugation as well as pretargeting purposes. [39][40][41] To perform this synthetic methodology, the novel [ 18 F]AlF-3, containing the NODA chelator instead of NOTA, was prepared and subsequently reacted with the TCO-functionalized-affibody molecule at room temperature via an IEDDA reaction. This methodology enables the radiofluorination of heatsensitive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…2729 Others have confirmed the AlF fluorination potential using RGD peptides and some simple derivatives of NODA. 3032 …”
Section: Introductionmentioning
confidence: 99%